2018
DOI: 10.1016/j.cub.2018.04.012
|View full text |Cite
|
Sign up to set email alerts
|

A Role for Mouse Primary Visual Cortex in Motion Perception

Abstract: Visual motion is an ethologically important stimulus throughout the animal kingdom. In primates, motion perception relies on specific higher-order cortical regions. Although mouse primary visual cortex (V1) and higher-order visual areas show direction-selective (DS) responses, their role in motion perception remains unknown. Here, we tested whether V1 is involved in motion perception in mice. We developed a head-fixed discrimination task in which mice must report their perceived direction of motion from random… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
54
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(58 citation statements)
references
References 64 publications
2
54
0
Order By: Relevance
“…Several groups have now successfully devised paradigms for studying evidence accumulation in rats and mice (Brunton et al ., ; Raposo et al ., ; Morcos & Harvey, ; Marques et al ., ; Pinto et al ., ). Specifically, Hanks et al .…”
Section: Brain Areas Causally Involved In the Accumulation Of Sensorymentioning
confidence: 98%
“…Several groups have now successfully devised paradigms for studying evidence accumulation in rats and mice (Brunton et al ., ; Raposo et al ., ; Morcos & Harvey, ; Marques et al ., ; Pinto et al ., ). Specifically, Hanks et al .…”
Section: Brain Areas Causally Involved In the Accumulation Of Sensorymentioning
confidence: 98%
“…5,6 ). Whereas the mouse, a genetically powerful animal model, has been used to study visually guided behavior [7][8][9] , and recently, circuits for cross-modal attention 10,11 , it has been debated whether mice are capable of exhibiting spatially well-resolved visual behaviors that are necessary to unpack the circuit basis of visuospatial attention, with just one recent study reporting success 6 .…”
mentioning
confidence: 99%
“…In addition, strong orientation tuning and direction selectivity are already present in the lateral geniculate nucleus [33][34][35], in contrast to the weakly tuned LGN neurons found in primates [36]. Finally, in contrast to primate V1 [9,18], mouse V1 contains a significant fraction of neurons that exhibit tuned responses to global coherent motion found in RDKs [3] and plaid pattern motion ( [37,38], though see [39]).…”
Section: Introductionmentioning
confidence: 96%
“…Although neurons selective for visual motion arise early in the visual system, extensive research in primates has shown that perception of coherent global motion independent of local motion relies on processing in specialized regions of visual cortex [1,2]. The cortical processing of coherent motion has been studied extensively in primates, but is not as well understood in the mouse, [1,2] although mouse visual cortical neurons are known to be well-tuned for coherent visual motion [3,4], and vision plays an important role in navigation [5], but the cortical organization of coherent motion processing is poorly understood. Recently developed techniques for measuring and manipulating neural activity in genetically identified neurons makes the mouse an attractive model system for investigating the neural circuitry underlying coherent motion processing [6,7].…”
Section: Introductionmentioning
confidence: 99%